2015
DOI: 10.1016/s2222-1808(15)60831-3
|View full text |Cite
|
Sign up to set email alerts
|

Home-based malaria management in children by women: Evidence from a malaria endemic community in sub-Saharan Africa

Abstract: 15Objective: To examine the medicines and dosage that mothers who engaged in home-16 based malaria management administer to children aged ≤ 5 years having signs and 17 symptoms associated with malaria. It was also to discuss the possibilities of designing an 18 effective home-based malaria management strategy. 19 Methods:The data were obtained from face-to-face semi-structured interviews 20 conducted with mothers in the Ugbowo Community of Benin City, Nigeria who were 21 selected using multi-stage systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Furthermore, 6.4% responded that malaria is caused by witchcraft. A total of 82.1% respondents had the knowledge that the best preventive practice is sleeping under nets followed by spraying insecticides (81%) then screening of windows with net (80%) which is also similar to report by Amaechi and Ukpai [19] and Eugene-Ezebilo [20]. An investigation by Msugh-Ter et al [21] revealed that most students make use of window nets as protection against mosquito bites 77.7% (233/300) followed by insecticide treated nets and insecticidal sprays while very few respondents 0.7% (2/300) made use of mosquito weeds as repellents.…”
Section: Introductionsupporting
confidence: 77%
“…Furthermore, 6.4% responded that malaria is caused by witchcraft. A total of 82.1% respondents had the knowledge that the best preventive practice is sleeping under nets followed by spraying insecticides (81%) then screening of windows with net (80%) which is also similar to report by Amaechi and Ukpai [19] and Eugene-Ezebilo [20]. An investigation by Msugh-Ter et al [21] revealed that most students make use of window nets as protection against mosquito bites 77.7% (233/300) followed by insecticide treated nets and insecticidal sprays while very few respondents 0.7% (2/300) made use of mosquito weeds as repellents.…”
Section: Introductionsupporting
confidence: 77%